PEMBUATAN BIODIESEL DARI RBDPO DENGAN KATALIS CANGKANG KEPAH - M. Yusuf Ritonga; Anda Putra (Talenta Publisher (Universitas Sumatera Utara), 2015)
Biodiesel is a low-emission diesel fuel substitute made from renewable resources and waste oil. The objective of the study was to study of CaO catalysts in biodiesel production from RBDPO with clam shell catalyst through calcinations of CaCO3 with temperature of 900oC and 3.5 hours will be obtained CaO content of 68,35%. Effect of various process variables such as type of catalyst, reaction time, amount of catalyst and molar ratio of Methanol / oil were investigated. The biodiesel properties like methyl ester content, density, viscosity, and flash point was compared with Indonesian Standard (SNI). Under the best condition, the maximum yield, purity, density, viscosity and flash point of biodiesel RBDPO respectively for 84,0179%, 97,98%, 875,47 kg/m3, 4,99 cSt and 122oC was obtained by using 12:1 molar ratio of methanol to RBDPO oil at 60oC, for a reaction time of 2 hours in the presence 5 wt% of CaO catalyst. The results of this research showed that heterogeneous catalysts CaO derived from clam shell suitable to be used as catalysts in biodiesel production.